PENGARUH CR, DER, EPS, DAN TINGKAT SUKU BUNGA TERHADAP RETURN SAHAM PERIODE 2017 – 2021 - Wahyuningsih, Julian; Susanti, Merry (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This study aimed to examine how current ratio, debt to equity ratio, earnings per share, and interest rates affected share returns in property and real estate companies listed on the Indonesia Stock Exchange (IDX) between 2017 – 2021. 95 data from property and real estate firms that were chosen using a purposive sampling technique are used in this study. EViews version 12 was used to process the secondary data. The outcome of the F test result indicate that the independent variable together does not significantly affect the dependent variable. The t test result reveals that current ratio, debt to equity ratio, and earnings per share do not significantly affect share return, while interest rates have a significant and negative influence on share return. The implication of this study is that investors need to consider the company's internal and external factors in making a share investment decision so that investors can minimize the investment risk.